Analysis of Public Perceptions and Participation in Household Waste Management in the Working Area of Waste Management Technical Implementation Unit of Tumpang District Malang Regency - Roosa, Lucy Cynthia; Khusaini, Mohammad; Kartikaningsih, Hartati (Postgraduate School of Universitas Brawijaya, 2023)
Population growth accompanied by activities in all fields affects the quantity and quality of waste produced. Community patterns and culture in managing waste currently still follow the old paradigm of collect-transport-dispose. This results in a buildup of waste which can shorten the life of the final landfill site (TPA) and impact the environment. Therefore, it is necessary to know the public's perception and participation in waste management to reduce the volume of waste. This research aims to determine and analyze the relationship between public perception and participation in household waste management. This research was conducted in the work area of the Waste Management Technical Implementation Unit, Tumpang District, Malang Regency. This research uses a quantitative approach supported by qualitative descriptive data collected through surveys and questionnaires. Based on research, it shows that the public's perception of household waste management is cumulatively positive and no negative perceptions were found. This means that there is no rejection from the community towards waste management efforts, but this positive perception is not supported by community participation. Keywords: household waste, perception, participation